The current state and prospects of X-ray computational tomography; Russian Journal of Nondestructive Testing; Vol. 52, iss. 4 - Chakhlov S. V. Sergey Vladimirovich; Osipov S. P. Sergey Pavlovich; Temnik A. K. Anatoly Konstantinovich; Udod V. A. Viktor Anatolievich (2016, 2016)
Title screen